2014
DOI: 10.1259/bjr.20140604
|View full text |Cite
|
Sign up to set email alerts
|

The value of real-time ultrasound elastography in chronic autoimmune thyroiditis

Abstract: In our study, we detected the stiffness ratio of the thyroid tissue in patients with CAT. The cut-off value should be helpful for diagnosis or follow-up of the recently developed lesions such as lymphoma, malign nodule, etc. based on CAT. This study should also encourage new studies about CAT and ultrasound elastography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 18 publications
8
33
1
2
Order By: Relevance
“…To the best of our knowledge, there are no studies in the literature about the use of ARFI in pediatric patients with Hashimoto thyroiditis. There were only a limited number of studies in adults, and only a few of these were performed with ARFI elastography . In a study by Sporea et al, the mean SWV of the thyroid gland in patients with Hashimoto thyroiditis (2.43 ± 0.58 m/s) was found to be significantly higher than that in healthy participants (2.00 ± 0.40 m/s).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no studies in the literature about the use of ARFI in pediatric patients with Hashimoto thyroiditis. There were only a limited number of studies in adults, and only a few of these were performed with ARFI elastography . In a study by Sporea et al, the mean SWV of the thyroid gland in patients with Hashimoto thyroiditis (2.43 ± 0.58 m/s) was found to be significantly higher than that in healthy participants (2.00 ± 0.40 m/s).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has evaluated the value of strain elastography for the differential diagnosis of SAT (29), and only one study has evaluated the value of strain elastography for differential diagnosis of HT (21).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Menzincioglu et al showed that SR is higher in HT than in normal thyroid parenchyma via RTE (21). However, their study group was relatively small (only 31 patients with HT) and had limited value.…”
Section: Chronic Autoimmune Thyroiditismentioning
confidence: 99%
“…Elastography was recently demonstrated to be an invaluable diagnostic method in differentiating between various pathologies in 283 patients with Hashimoto's thyroiditis (16,25). A strain index ratio and cut-off value of the thyroid tissue was higher in patients with chronic autoimmune thyroiditis compared with the values in normal thyroid parenchyma in RTE, suggesting that these two diagnostic parameters may be helpful for diagnosis or follow-up of lymphoma and malign nodules (26). Furthermore, the diagnostic values of CEUS or RTE alone were previously assessed in the characterization of thyroid nodules (16).…”
Section: Introductionmentioning
confidence: 99%